2021
DOI: 10.1161/strokeaha.120.032487
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 90-Day Outcome After Thrombectomy: Baseline-Adjusted 24-Hour NIHSS Is More Powerful Than NIHSS Score Change

Abstract: Background and Purpose: The National Institutes of Health Stroke Scale (NIHSS) measured at an early time point is an appealing surrogate marker for long-term functional outcome of stroke patients treated with endovascular therapy. However, definitions and analytical methods for an early NIHSS-based outcome measure that optimize power and precision in clinical studies are not well-established. Methods: In this post-hoc analysis of our prospective observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…In line with our results, all have demonstrated that early neurological assessment after MT in anterior circulation strokes serves as a reliable predictor for functional outcome at day 90. [1][2][3][4] Those studies also reported that patients with successful recanalization had significantly lower NIHSS 24 hours scores with higher probability of functional independence at 90 days, which is also concordant with our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, all have demonstrated that early neurological assessment after MT in anterior circulation strokes serves as a reliable predictor for functional outcome at day 90. [1][2][3][4] Those studies also reported that patients with successful recanalization had significantly lower NIHSS 24 hours scores with higher probability of functional independence at 90 days, which is also concordant with our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…32 Another study reported that a 24-hour NIHSS score of ≤ 7 was an independent predictor of good outcome after 3 months. 33 Previous studies reported an association between collateral circulation status and outcome after MT. 34 We, however, failed to prove this association in our cohort where good outcome had been achieved independently irrespective of the collateral circulation status.…”
Section: Discussionmentioning
confidence: 99%
“…The IMTbif still showed independent association with neurological outcomes in diabetic patients, even taking the widely acknowledged strong stroke severity predictor NIHSS into account as a confounding variable statistically. 24 …”
Section: Discussionmentioning
confidence: 99%